Perancangan Sistem HACCP di Plant 2 PT X - Rellya Speedya Sugianto; Togar W.S. Panjaitan (Jurnal Titra, 2014)
PT X is a company which produces vegetable oil with copra and Crude Palm Oil (CPO) as the raw material. PT X wants to supply international company, such as Kraft Foods. Kraft Foods has several regulations for prospective suppliers and of them is HACCP documentation. The design of HACCP system in this thesis is done for RBD (Refined Bleached Deodorized) CNO (Coconut Oil), Olein, and Stearin which produced at Plant 2 PT X. The first Critical Control Point (CCP) are sack fiber, sponge, and metal at the output filtering process. The controlling of the first CCP is done by monitoring the pressure gauge when the filling process is done. The second CCP are tee cable, animal pest, and cloud filter fiber at stearin strainer. This CCP is controlled by stearin strainer cleaning before and after the production process. There are several differences between the HACCP system at PT X and Kraft Foods, such as the quality standard, risk analysis, and documentation format. Based on the analysis that has been done, the percentage of processes belong to Prerequisite Program for RBD CNO are 32,26%; RBD Olein are 35,48%; and RBD Stearin are 33,33%. The percentage of processes belong to Critical Control Point for RBD CNO and Olein are 3,23%; RBD Stearin are 3,33%.